Membangun Sistem Ekonomi Berkeadilan: Telaah atas Pemikiran Muhammad Baqir Al-Sadr - Agus Waluyo Nur (IAIN Salatiga, 2011)
This writing is aimed to explore the Baqir Sadr’s ideas on Islamic economics. It is important that his ideas have fundamental differences with other Islamic economic thinkers. They have an argument that the economic problems are caused by the scarcity of economic resources comparing with unlimited human needs. But according to Sadr, economic problems are caused by the uneven distribution of wealth. Sadr also distinguishes between economic sciences with the economic doctrine. Islamic economics is not theoretical sciences, but it is a doctrine of Islam in pursuit of economic life. His basic ideas of Islamic economic was contained in his writing (Iqtisaduna) which studied the theory of production and distribution. Unlike the known Islamic economics at the moment, the Islamic economic system on Sadr’s perspective is more comprehensive, profound, and rooted on Islamic justice values.